A Participatory Culture for Developing an Inclusive Environment in Higher Education - Dhyah Ayu R. Widyastuti; B.K. Prihandono; A.B. Pramudyanto; L.A. Rudwiarti (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Increasing understanding, concern, partiality, and equality for persons with disabilities is important. One disparity can be found in the educational area. The role of the government to increase the capability of this group is the enactment of Law No. 8 of 2016, which substantially provides accessibility to persons with disabilities. The education environment needs to participate in building a disability-friendly education climate. This paper presents a higher education case study for students with special needs at Universitas Atma Jaya Yogyakarta. The research uses the Inclusive Participatory Action Research approach to explore problems, design program planning, management, and implementation of efforts to create a disability-friendly environment. Through this approach, persons with disabilities are the subject of planning, implementation, and evaluation. It means that the active involvement of the target group is essential in this effort. The results show that participatory culture is essential in building an inclusive environment in higher education. The commitment and cooperation of all university members can realize a disability- friendly environment. The focus of this article includes (a) efforts to build a disability-friendly environment; (b) disability-friendly education approach; (c) challenges in the implementation and environmental impacts of inclusion in higher education. Hopefully, this idea can contribute to building an inclusive environment in an educational institution.